Approaches to management and treatment of Nhova among indigenous practitioners and selected Christian churches - Govere, Nolia Fadzai (Midlands State University, 2018)
The study focuses on the different approaches used by indigenous practitioners, Johane Masowe church and AFM in the management and treatment of nhova in Zvishavane. It is a comparative study that seeks to impact and interrogate the convergences and divergences among the Christian churches and indigenous practitioners. The study was guided by Afrocentricity particularly Karenga (1993)‟s ideas on multiculturalism. Utilising interviews questionnaires and focus group discussions, the study established that there are several approaches used by both Christian churches and indigenous practitioners. These include salt, cooking oil, soil, indigenous herbs, Maduma (waist and neck strings) and Muteuro (prayer). The study establishes convergences between indigenous practitioners and Johane Masowe since both make use of, salt, cooking oil and maduma. AFM presented a different scenario because they believe in Jesus Christ as a healer, have faith in the power of prayer to heal every disease and going to hospital. The research therefore presents a case where there is critical need to respect differences.